A Simulation Approach to Improve Assembly Line Performance - VILLARREAL, BERNARDO; Roble Alanis, Maria (International Journal of Industrial Engineering: Theory, Applications and Practice, 2011)
A fundamental characteristic of today´s competitive environment is the need for shorter product life cycles and increased demands for customization. These aspects are difficult to satisfy operating with traditional production lines. The development of JIT U-lines has been an emerging response to compete in this type of environment. The present work describes the utilization of simulation to guide the improvement efforts during the redesign of a traditional assembly line system in a Mexican manufacturing facility. The approach taken is a two-level one. A macro model that simulates operations at plant level and assesses the synchronization of material flows between warehouses and assembly lines and is used to determine materials handling resource requirements and overall layout options. The second level is detailed and at the line level. Here, Balancing, operator assignments and buffer sizes are defined for each line. The space required and detailed layout for each line are also determined.